Individual tax fairness in developing country: perceptions among Malaysian tax professionals / Azwanis Azemi - Azemi, Azwanis (Universiti Teknologi MARA Cawangan Selangor, 2020)
Tax fairness has been used as one of the important determinants for tax compliance. Good perception of tax fairness would encourage taxpayers to comply with tax law to avoid any unreported and unpaid revenue to the government. Individual taxpayers are required to pay income tax, and they may engage with tax agents for their tax computation. This situation motivates this study to look into further dimensions of tax fairness by looking at tax agents’ perception as they are the important person to consult and give advice on tax matters. The main objective of this study is to propose the dimensions of individual tax fairness based on tax agents’ perceptions in Malaysia, and secondly, is to study on the prior literature and classify the dimensions of individual tax fairness that used similar measurement of Gerbing’s study. Sets of survey questionnaires were distributed at two tax conferences held in Kuala Lumpur, and the final data of 196 responses were analysed by exploratory factor analysis (EFA). The results indicated that tax agents identified six dimensions of tax fairness, and regardless of developed or developing countries, the numbers of dimensions of tax fairness could be identified more, depending on the level of individuals’ tax practice and knowledge. These results are expected to provide the implications either in theory and practice of tax fairness’ dimensions in Malaysia.